Demografske karakteristike hrvatskih naselja župe Bogdašina u XVIII. stoljeću - Vegh, Andor (SlavVaria, 2026)
Demographic characteristics of Croatian settlements of Bogdása parish in the 18th century. In this paper, we supplement our previous research on Croatian settlements along the Drava River east of the town of Barč in the 18th and 19th centuries. In this paper, as in the previous one, through a quantitative analysis of birth registry data and a qualitative analysis of surnames in the settlements of Drvljanci/Dravljanci (Révfalu), Križevci (Drávakeresztúr), and Starin (Drávasztára), we attempt to point to some settlement processes. With the help of available literature and comparative methods with previously conducted analyses (Martinci, Lukovišće, Novo Selo, Potonja, Brlobaš), we provide an overview of the settlement that created the basis for the further demographic and social development of these settlements.